2023
DOI: 10.3389/fnrgo.2023.1104873
|View full text |Cite
|
Sign up to set email alerts
|

A review of cyber vigilance tasks for network defense

Abstract: The capacity to sustain attention to virtual threat landscapes has led cyber security to emerge as a new and novel domain for vigilance research. However, unlike classic domains, such as driving and air traffic control and baggage security, very few vigilance tasks exist for the cyber security domain. Four essential challenges that must be overcome in the development of a modern, validated cyber vigilance task are extracted from this review of existent platforms that can be found in the literature. Firstly, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(24 citation statements)
references
References 109 publications
(316 reference statements)
0
21
0
Order By: Relevance
“…Guidetti et al ( 2023 ) identified cyber-cognitive elements of software design and three central challenges in creating a cyber vigilance task. Firstly, civilian researchers cannot easily access existent vigilance tasks developed within a military context (Paul, 2014 ; Gutzwiller et al, 2015 ).…”
Section: Cyber Vigilance Tasksmentioning
confidence: 99%
See 4 more Smart Citations
“…Guidetti et al ( 2023 ) identified cyber-cognitive elements of software design and three central challenges in creating a cyber vigilance task. Firstly, civilian researchers cannot easily access existent vigilance tasks developed within a military context (Paul, 2014 ; Gutzwiller et al, 2015 ).…”
Section: Cyber Vigilance Tasksmentioning
confidence: 99%
“…The WACDT was therefore developed by civilians to expand cyber vigilance research beyond the military. Secondly, existent cyber vigilance tasks could be presented on a single computer monitor (McIntire et al, 2013 ; Mancuso et al, 2014 ; Sawyer et al, 2016 ; Guidetti et al, 2023 ). However, modern network defense is too complex a role to perform on a single computer monitor (D'Amico et al, 2016 ; Axon et al, 2018 ).…”
Section: Cyber Vigilance Tasksmentioning
confidence: 99%
See 3 more Smart Citations